Programma: 17 juni Banda Mexe Com Tudo; 18 juni Mudhoney; 19 juni Dr Feel Good; 21-24 juni How Aids changes our world
Programma: 17 juni Banda Mexe Com Tudo; 18 juni Mudhoney; 19 juni Dr Feel Good; 21-24 juni How Aids changes our world.